(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
This piece of writing succinctly outlines the highlights of the Digital India initiative taken by the Government of India in 2015.PM Narender MODI at the helm of the India spearheaded the task of launching series of initiatives like Make in India, Digital India and various others that not only empower the government but also its citizen. The underlying intent of this programme is to rebuild, redesign and reinvent India with an aid of information and technology and building a perception of “Go Digital or Making India Digital” across India. The rationale behind the programme is to cater the benefits given by the government directly to the citizen and eliminating the role of intermediaries who are engaged in the service of serving the benefits to its citizen. This paper presents the opportunities and challenges in the making India digital savvy. The views expressed are founded on the basis of facts and figure available on paper and digital literature.